(4x^3-6x^2+5)-(8x^2+3x-6)=

Simple and best practice solution for (4x^3-6x^2+5)-(8x^2+3x-6)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4x^3-6x^2+5)-(8x^2+3x-6)= equation:

Simplifying
(4x3 + -6x2 + 5) + -1(8x2 + 3x + -6) = 0

Reorder the terms:
(5 + -6x2 + 4x3) + -1(8x2 + 3x + -6) = 0

Remove parenthesis around (5 + -6x2 + 4x3)
5 + -6x2 + 4x3 + -1(8x2 + 3x + -6) = 0

Reorder the terms:
5 + -6x2 + 4x3 + -1(-6 + 3x + 8x2) = 0
5 + -6x2 + 4x3 + (-6 * -1 + 3x * -1 + 8x2 * -1) = 0
5 + -6x2 + 4x3 + (6 + -3x + -8x2) = 0

Reorder the terms:
5 + 6 + -3x + -6x2 + -8x2 + 4x3 = 0

Combine like terms: 5 + 6 = 11
11 + -3x + -6x2 + -8x2 + 4x3 = 0

Combine like terms: -6x2 + -8x2 = -14x2
11 + -3x + -14x2 + 4x3 = 0

Solving
11 + -3x + -14x2 + 4x3 = 0

Solving for variable 'x'.

The solution to this equation could not be determined.`